Kazakhstan beef cattle indices - Bissembayev, A. T.; Shamshidin, A. S.; Nassambaev, E. G.; Seitmuratov, A. E.; Kasenov, J. M.; Abylgazinova, A. T.; Gubashev, N. M. (International Journal on Emerging Technologies, 2020)
The paper presents the results of the industrial calculation of breeding value indices for the Auliekol breed. The methodology for index evaluation calculation with the use of the BLUP AM statistical method with the construction of the animal genetic model was exercised. The predicted breeding value indices were calculated using three productive traits: live weight at birth, at weaning, and at 12 months of age. A brief outline of the creation of the Auliekol breed was given and advantages of the original breeds participating in the crossing were emphasized. The article presents equations of a linear biometric model of the animal, which considers the influence of a variety of factors and effects on the evaluated trait of productivity. The effect of all factors included in the model was considered simultaneously in the calculation process. As a result of solving the linear equations of biometric models of animals using the BLUP method, genetic estimates of their productivity were obtained according to economically useful characteristics. Estimates of factors and effects of influence on productive traits were obtained as well. В статье представлены результаты промышленного расчета показателей племенной ценности для аулиекольской породы. Разработана методика расчета оценки индекса с использованием статистического метода BLUP AM с построением генетической модели животных. Прогнозируемые индексы племенной ценности были рассчитаны с использованием трех продуктивных признаков: живой вес при рождении, при отъеме и в возрасте 12 месяцев. Был дан краткий план создания аулиекольской породы и подчеркнуты преимущества оригинальных пород, участвующих в скрещивании. В статье представлены уравнения линейной биометрической модели животного, которая учитывает влияние множества факторов и воздействий на оцениваемый признак продуктивности. Влияние всех факторов, включенных в модель, учитывалось одновременно в процессе расчета. В результате решения линейных уравнений биометрических моделей животных методом BLUP получены генетические оценки их продуктивности по экономически полезным характеристикам. Получены оценки факторов и эффектов влияния на продуктивные признаки.
Keywords: импакт-фактор 2020; периодическое издание; скопус; дальнее зарубежье; мясное скотоводство; зарубежное издание; научный журнал